AUDITORS’ EXPECTATION GAP IN THE NIGERIAN BANKING INDUSTRY - Bassey, Bassey Eyo; Effiong, Charles; Bessong, Peter Kekung; Uromg, Alice (International Journal of Psychosocial Rehabilitation, 2020)
The study described what audit expectation gap is in the Nigeria banking industry. It aimed to ascertain if Nigerian banks users affirm to the responsibility of auditors to detect and prevent fraud. The research adopted a cross-sectional study using three cities in Nigeria Calabar, Port Harcourt and Uyo taking into consideration views of users of financial statement in the Nigerian banking sector. Data were collected via questionnaire. Of the 450 copies distributed, three hundred and seventy-six (376) copies of the instrument were found to be useful and independent T-test was used to evaluate the data collected from these respondents. The study found that user of financial statements in the Nigerian banking sector does not concur to assurance of auditor’s responsibility in detecting and preventing fraud. It was therefore concluded that there is existence of gap in the responsibility of auditors practice in the Nigerian banking sector. It was recommended amongst others, that statutory auditors 'roles and obligations should be properly stated and incorporated by regulatory authorities to ease detection and prevention of fraud by the auditors. The public should be informed on current key on auditor’s role and duties.